Factors affecting housing purchase decision in Vietnam - Le, Thi Phuong Loan (Journal of Finance - Marketing Research, 2023)
Housing is an essential asset for households, and owning a home is a dream of many people, For a country with one of the largest populations in the world such as Vietnam, owning a house for low-income employees is even more desirable to low-income people. Many low-income people are disadvantaged groups in society, so building houses that meet the needs of disadvantaged groups always has a positive impact on socio-economic development. The article uses a survey method combined with regression analysis to identify factors affecting the decision to buy housing in Vietnam, including income, location, quality of work, living environment, prices, and references. These are factors associated with the character and local characteristics of Vietnamese people.